Case Study : KR Enterprise / Nabila Husna Mohamad Rodzi - Mohamad Rodzi, Nabila Husna (2020)
KR Enterprise is a small company formed in Pantai Getting, Tumpat, Kelantan. The owner of the company, Teku Rahaman bin Tuan Mat or which he preferred to be called as Ku Rahaman has started the business for 10 years ago together with his wife and children. ‘budu’ is their main product. ‘budu’ is a food which is a fish sauce made from fermented anchovies. The owner of this company adopts an open mindset where he saw many opportunities despite a lot of competition. He tried to make ‘budu’ with most traditional way as possible as he does not add any preservative or any flavouring in the ‘budu’